Food and Culture in Karuna Riazi’s The Gauntlet (2017) - Sa'adah, Sufi Ikrima; Nuristama, Ramadhina Ulfa (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Karuna Riazi’s The Gauntlet (2017) falls under the middle-grade fantasy genre. This novel narrates the adventure of Farah Mirza, together with her friends, to save her little brother and other children who are trapped in a mechanical board game called The Gauntlet of Blood and Sand. The fast-paced narrative adds its appeal with a rich portrayal of food in a South Asian Muslim culture. This study, then, examines how the culinary elements in the story serve as the markers that connect the protagonist, Farah Mirza, to her cultural identity. Employing a qualitative textual analysis, this research collects the data from any depiction of food and the situation in which the food is served. The data analysis identifies food depictions related to family gatherings, tea time, and breakfast. The analysis reveals that these food scenes reflect cultural values such as hospitality, resilience, and familial warmth. These findings suggest that Riazi’s portrayal of food emphasizes Farah’s Muslim identity while fostering intercultural appreciation.